2015
DOI: 10.1108/ijmf-08-2013-0086
|View full text |Cite
|
Sign up to set email alerts
|

Institutional investors, information asymmetry and stock market liquidity in France

Abstract: Purpose – The purpose of this paper is to examine the effect of institutional investors’ ownership and type on information asymmetry and stock market liquidity in France. Design/methodology/approach – The sample includes 162 French-listed firms from 2007 to 2009. The methodology relies on linear regressions using the method of ordinary least square. Before examining the interaction between liquidity and institutional investors, the autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 47 publications
8
47
0
3
Order By: Relevance
“…Indeed, the studies of Attig et al, (2006), Brockman and Chung (2001), and Ajina et al, (2015) found that stock pricepositively correlates with liquidity.…”
Section: Stock Pricementioning
confidence: 99%
“…Indeed, the studies of Attig et al, (2006), Brockman and Chung (2001), and Ajina et al, (2015) found that stock pricepositively correlates with liquidity.…”
Section: Stock Pricementioning
confidence: 99%
“…In the same context, Ajina et al (2015) indicated that institutional share-ownership appeared to mitigate bid-ask spreads and enhance stock liquidity. Owing to the diverse portfolios of institutional investors, they trade frequently.…”
Section: Ownership Structure and Stock Market Liquiditymentioning
confidence: 99%
“…Meanwhile, shareholder concentration was reported to have a negative effect on liquidity of the French market by Ajina and Lakhal (2010). Evidently, the controlling shareholder (informed investor), may lessen the information volume on the market and this would lead to high adverse selection costs.…”
Section: Ownership Structure and Stock Market Liquiditymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, an organization should inevitably meet the expectations and needs of the shareholders and stakeholders including suppliers, customers, government, communities, and creditors as well [7]. The financial corruptions and discriminative behaviors in the organizations have attracted the attention of both scholars and policymakers in recent years [8]. This leads to need for maintaining strict monitoring and control of organizations in order to protect the interests of shareholders and stakeholders [9].…”
Section: Introductionmentioning
confidence: 99%